1991
DOI: 10.1029/90ja01837
|View full text |Cite
|
Sign up to set email alerts
|

Poynting flux measurements on a satellite: A diagnostic tool for space research

Abstract: The first satellite observations of the total field‐aligned component of the quasi‐dc Poynting flux are presented for two passes over the polar region, one in the noon sector and one in the afternoon. The energy input due to electron precipitation is also presented. In the noon pass the downward Poynting flux in the auroral oval was comparable to the kinetic energy input rate. The peak electromagnetic energy input rate of 6 ergs/(cm² s) equaled the peak particle input while the integrated electromagnetic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 11 publications
11
106
0
Order By: Relevance
“…For this event however, the maximum electromagnetic energy flux was 50 mW/m 2 , considerably higher than typical maxima inferred from radars and assimilation techniques. It is also at the high end of energy fluxes observed from satellites which were observed at auroral latitudes (Kelley et al, 1991;Gary et al, 1995). Our result implies that the localized heating near the magnetic pole during this event was particularly strong and should be associated with a strong localized thermospheric temperature enhancement and corresponding upwelling comparable in intensity to that occurring at auroral latitudes during active times.…”
Section: Discussion and Summarymentioning
confidence: 55%
“…For this event however, the maximum electromagnetic energy flux was 50 mW/m 2 , considerably higher than typical maxima inferred from radars and assimilation techniques. It is also at the high end of energy fluxes observed from satellites which were observed at auroral latitudes (Kelley et al, 1991;Gary et al, 1995). Our result implies that the localized heating near the magnetic pole during this event was particularly strong and should be associated with a strong localized thermospheric temperature enhancement and corresponding upwelling comparable in intensity to that occurring at auroral latitudes during active times.…”
Section: Discussion and Summarymentioning
confidence: 55%
“…Moreover, surveys of large-scale Poynting fluxes were primarily performed in the ionospheric altitudes. Low-altitude satellite data and global circulation models showed that these are directed predominantly downward, which means dominance of the magnetospheric driver [Kelley et al, 1991;Gary et al, 1995;Deng et al, 2008]. Upward Poynting fluxes are generally weaker but exist especially during a larger southward IMF [Gary et al, 1995], indicating presence of escaping electromagnetic energy associated with large-scale electric fields from the ionosphere toward the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Poynting fluxes have been calculated for the ionosphere for some time (Kelley et al 1991;Wilder et al 2012;Cosgrove et al 2014). DMSP routinely measures the ion drifts from which the convective electric field (E) can be extracted, as well as magnetic perturbations (dB) about the Earth's magnetic field.…”
Section: Ionospheric Response To Solar Wind Forcing -Observationsmentioning
confidence: 99%